Does the COVID-19 pandemic affect social-ecological resilience of organic rice production system in Chiang Mai Province, Thailand? - Panpakdee, Chaiteera; Palinthorn, Fakjit (Forest and Society, 2021)
The purpose of this study was to investigate how the COVID-19 pandemic affects the organic rice production system in four districts of Chiang Mai Province. Eight organic farmers were purposefully chosen as informants because they have possessed forty-seven resilience components (SERCs) needed to cope with all kinds of social-ecological change. They were asked using a structured questionnaire to assign each SERC’s contribution value before and after the COVID-19 pandemic, in which each time scoring must be coupled with entailed explanations. Then, the paired samples t-test was run to compare such means of SERCs’ contribution values to examine whether their organic rice production’s resilience was affected by the pandemic and how. Results showed the means of SERCs before and after the pandemic have no significant difference as the p-value is 1.00 at the 95% confidence interval. This meant the pandemic does not influence the organic rice production’s social-ecological resilience. But several practices and qualifications were found varying from the original to make production more suitable. The dependence on household labor and that on mutual labor exchange were respectively increased and decreased in their roles in resilience building. Labor availability was interrupted by the social distancing protocol that had restricted people from gathering. Besides, the household accounts recording was adopted more than usual for being seen as a solution to improving the household economy during the time of financial vulnerability. Importantly, relying on local goods was remarkably recognized for increased importance. This was an attempt to get access to materials possibly free from the COVID-19 contamination because of the absent transportation. These findings provide two key interests. They can be applied as a framework not only to strengthen agricultural resilience but also to propose a blueprint of coping mechanisms against the pandemic at a mass scale.